Problem-based learning model: Can it improve learning outcomes for long serve in badminton? - Suryadi, Didi; Samodra, Y Touvan Juni; Gustian, Uray; Yosika, Ghana Firsta; Sastaman B, Putra; Dewintha, Rezza; Saputra, Eko (Edu Sportivo: Indonesian Journal of Physical Education, 2023)
This study aims to prove the improvement of learning outcomes from long service techniques in badminton games through problem-based learning models. The type of study used is the classroom action research design. The subjects of this study were students of Senior High School 2 Sukadana in the 2021–2022 school year, especially class X IPA students, totaling 25 students. The results showed an increase in cycle I, namely 28% completion, but there were still many students who were not complete, with a percentage of 72%. Based on the results in cycle II, it shows that there is a difference in the percentage achieved, namely, in cycle I, 28% of students are complete, and the last in cycle II shows a percentage of 92% of students are complete on the learning outcomes of the badminton long serve. The conclusion proves that the problem-based learning model can improve long-term service skills in badminton games. This research has provided new references related to physical education learning, where these results recommend that the problem-based learning model can be applied to solve badminton long serve problems.